2019
DOI: 10.1063/1.5111763
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular architecture and complex viscosity

Abstract: General rigid bead-rod theory [O. Hassager, “Kinetic theory and rheology of bead-rod models for macromolecular solutions. II. Linear unsteady flow properties,” J. Chem. Phys. 60(10), 4001–4008 (1974)] explains polymer viscoelasticity from macromolecular orientation. By means of general rigid bead-rod theory, we relate the complex viscosity of polymeric liquids to the architecture of axisymmetric macromolecules. In this work, we explore the zero-shear and complex viscosities of 24 different axisymmetric polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Recently, Kanso et al 14 showed that the virus structure governs its rotational diffusivity. Specifically, using the general rigid bead–rod theory 23 (and references therein), they showed that the virus rotational diffusivity descends monotonically with its number of peplomers. The recent study by Kanso et al 14 opens exciting possibilities for future research relating to the structure of CoV and its associated modeling.…”
Section: A New Weather-dependent Transmission Ratementioning
confidence: 99%
“…Recently, Kanso et al 14 showed that the virus structure governs its rotational diffusivity. Specifically, using the general rigid bead–rod theory 23 (and references therein), they showed that the virus rotational diffusivity descends monotonically with its number of peplomers. The recent study by Kanso et al 14 opens exciting possibilities for future research relating to the structure of CoV and its associated modeling.…”
Section: A New Weather-dependent Transmission Ratementioning
confidence: 99%
“…By low frequency, we mean low Deborah number, that is λω < 1. In this paper, from general rigid bead-rod theory [6,5,11,12,13,14], we arrive at an interesting explanation for these descents. We explore the effects of branching along a straight chain in small-amplitude oscillatory shear flow, and thus, on the complex viscosity, and thus, on the van Gurp-Palmen plots.…”
Section: Imentioning
confidence: 76%
“…INTRODUCTION Since its conception in [1,2,3], the complex viscosity has become by far the most commonly measured viscoelastic property for exploring the physics of polymeric liquids. Interpreting the measured frequency dependences of both the real and (minus) the imaginary parts of the complex viscosity in terms of polymer structure remains an important challenge [4,5,6]. Much progress along these lines has been achieved experimentally.…”
Section: Imentioning
confidence: 99%
“…All solutions and solvents were optically clarified by filtering through 0. 22 were measured using the equation 2:…”
Section: Characterization Size Exclusion Chromatography (Sec)mentioning
confidence: 99%
“…These studies include various fields of research, such as macrophase and microphase separation [3][4][5], gelation [6][7][8], crystallization [9,10] and association phenomena [11][12][13]. The progress in this area is closely related to the advances in the synthesis of well-defined macromolecular structures having the maximum control over the molecular characteristics and the architecture [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%